2003
DOI: 10.1002/jso.10242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiation and cell implantation on wound healing in a rat model

Abstract: Cell implantation holds promise for decreasing the effect of radiation on healing of irradiated wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…We have shown previously that injection of non-irradiated autologous fibroblasts (or bone marrow stromal cells) into an irradiated superficial wound site in rats can result in improved wound strength but using a deep wound model in rat hind limb we found that such injections are of limited value in improving wound strength [10,17,51]. Overall our results suggest that factors other than the radiosensitivity of the skin fibroblasts must play a critical role in wound healing in deep wound sites associated with surgery for STS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We have shown previously that injection of non-irradiated autologous fibroblasts (or bone marrow stromal cells) into an irradiated superficial wound site in rats can result in improved wound strength but using a deep wound model in rat hind limb we found that such injections are of limited value in improving wound strength [10,17,51]. Overall our results suggest that factors other than the radiosensitivity of the skin fibroblasts must play a critical role in wound healing in deep wound sites associated with surgery for STS.…”
Section: Discussionmentioning
confidence: 87%
“…Radiation leads to reduced fibroblast proliferative capability and function and this might be expected to impact negatively on the normal tissue response [10,17]. In a previous study we demonstrated that skin fibroblasts from individuals who developed wound healing complications following pre-operative radiotherapy had no detectable differences in radiosensitivity in vitro but tended to show a smaller reduction in early proliferation after irradiation [2].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Radiation and chemotherapy are believed to inhibit wound healing presumably by prevention of collagen synthesis [6,8]. Preoperative EBRT combined with IOERT increases the efficacy of radiation to the tumor bed, while ostensibly limiting morbidity to surrounding normal tissue, thus potentially minimizing the long-term adverse effects of radiation treatment [2,10,13].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that endogenous infection and bacterial toxins are crucial to increased mortality after radiation and burn (52). Several studies using animal models of radiation injury and wounds have shown that radiation exposure delays wound healing (53)(54)(55)(56)(57)(58). Thermal injury alone can lead to delayed wound healing, increased susceptibility to sepsis and multiorgan failure (59,60), and additional injuries can exacerbate these immunological complications.…”
Section: Radiation and Thermal Injury (Burns) Or Woundsmentioning
confidence: 99%